2017
DOI: 10.1016/j.cagd.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Bézier developable surfaces

Abstract: In this paper we address the issue of designing developable surfaces with Bézier patches. We show that developable surfaces with a polynomial edge of regression are the set of developable surfaces which can be constructed with Aumann's algorithm. We also obtain the set of polynomial developable surfaces which can be constructed using general polynomial curves. The conclusions can be extended to spline surfaces as well.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…As expected, when ν ≡ 0, no term along the projection direction appears and then σ ≡ 1. In this case, we recover the results for Bézier developable surfaces [19].…”
Section: Reparametrisation Of Rational Ruled Surfacessupporting
confidence: 78%
See 2 more Smart Citations
“…As expected, when ν ≡ 0, no term along the projection direction appears and then σ ≡ 1. In this case, we recover the results for Bézier developable surfaces [19].…”
Section: Reparametrisation Of Rational Ruled Surfacessupporting
confidence: 78%
“…In [17,18] Bézier developable patches are constructed by applying affine transformations to the first cell of the control net of the patch. It is shown in [19] that this construction produces all Bézier developable surfaces with a polynomial edge of regression. This construction has been extended to spline developable surfaces [20,21] and to Bézier triangular surfaces [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fernández-Jambrina proposed a linear algorithm to construct B-spline control nets for spline developable where five free parameters were applied to control vertices [12]. Developable surfaces were constructed with Bézier patches using Aumann's algorithm to form a polynomial edge of regression [13].…”
Section: Surface Flattenability Improvementmentioning
confidence: 99%
“…Finally, in [24] it is shown that the developable surfaces which can be constructed with Aumann's algorithm are the ones with a polynomial edge of regression. This poses an interesting problem.…”
Section: Introductionmentioning
confidence: 99%